Utility of a Nurse-Led Pathway for Patients with Acute Venous Thromboembolism Discharged on Rivaroxaban: A Prospective Cohort Study - Lim, Ming Sheng; Indran, Tishya; Cummins, Anita; Bennett, Ashwini; Wood, Erica; Brown, Susan; McQuilten, Zoe; Tran, Huyen; Epi, Master Clin; Chan, Noel C.; Chunilal, Sanjeev (Seminars in Thrombosis and Hemostasis, 2019)
The highest risk of adverse events for patients with acute venous thromboembolism (VTE) is during the early anticoagulation period. However, no established model exists for early clinical monitoring of patients treated with non–vitamin K antagonist oral anticoagulants (NOACs). The authors' aim was to evaluate the utility of a nurse-led pathway to minimize adverse events in acute VTE patients starting on rivaroxaban. The rivaroxaban VTE treatment pathway is a prospective cohort study of consecutive patients with objectively confirmed VTE between July 2015 and May 2017. Primary outcome was the proportion of patients identified at major risk of adverse events (bleeding or recurrent VTE). Secondary outcomes were rates of interventions, major or clinically relevant nonmajor bleeding (CRNMB), recurrent VTE, and all-cause mortality at 90 days. Among 304 participants, 5% (n = 15) were identified to be at major and 9% (n = 28) at possible risk for adverse events. Appropriate interventions to prevent harm were required in 40 patients. Rates of major bleeding, CRNMB, recurrence, and all-cause mortality were 0.3% (95% confidence interval [CI]: 0.1–1.8), 7.2% (95% CI: 4.8–10.7), 1.0 (95% CI: 0.3–2.9), and 1.6% (95% CI: 0.7–3.8), respectively. In conclusion, following discharge of acute VTE patients, a nurse-led pathway identified one in seven (14%) patients at major or possible risk of adverse events. Preemptive interventions to reduce harm translated into the low rates of bleeding and recurrence. The authors' experience highlights the feasibility and importance of a structured clinical surveillance pathway for acute VTE patients initiating NOAC therapy.
Keywords: adverse drug event; clinical pathways; nurse-led pathway; rivaroxaban; venous thromboembolism